2019
DOI: 10.3389/fneur.2019.00830
|View full text |Cite
|
Sign up to set email alerts
|

Postural Instability in Subjects With Usher Syndrome

Abstract: This study investigated postural performances and vestibular impairment in Usher patients. The three groups studied were: 11 patients with Usher type I (with visual and vestibular impairment), 14 patients with Usher type II (with only visual impairment), and 14 healthy control subjects. Postural stability was measured with a Framiral Multitest Equilibre platform with three visual conditions: eyes open (EO), eyes closed (EC), and vision disturbed by optokinetic stimulation (OPT), and two different postural cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(42 reference statements)
3
7
0
Order By: Relevance
“…We confirm previous reports identifying an overall aging effect on postural stability 32 . Our posturography data further support and expand upon observations by Caldani et al 17 that patients with Usher syndrome have reduced postural stability that results from deficits in visual and vestibular contributions to balance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirm previous reports identifying an overall aging effect on postural stability 32 . Our posturography data further support and expand upon observations by Caldani et al 17 that patients with Usher syndrome have reduced postural stability that results from deficits in visual and vestibular contributions to balance.…”
Section: Discussionsupporting
confidence: 92%
“…These findings have implications for personalized and targeted counseling and (re)habilitation of postural stability and balance in patients with Usher syndrome. This study also extends knowledge of postural stability in USH1 and USH2, which has been previously limited to one study in a genetically confirmed population, 17 and supplements the comprehensive report of variable SOT findings in USH3 39 …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Segregation studies, by Sanger sequencing, confirmed the presence of this pathogenic variant in heterozygosity in both parents, and the absence in the heathy sister (Figure 3). Although the kyphosis presented by our proband could be, at least partially, explained by the vestibular impairment, the other musculoskeletal complaints are not associated with Usher syndrome 34 . NEB pathogenic variants are implicated in the nemaline myopathy type 2 (NEM2, OMIM#256030), mainly characterized by early‐onset muscle weakness, predominately in proximal limb muscles with a high variability, ranging from mild to severe 35 .…”
Section: Resultsmentioning
confidence: 53%
“…Indeed, preserved low frequency canal function can be observed in some peripherical inner ear diseases with selective canal impairment (reduced middle and high frequency canal function with normal low frequency canal function -e.i. Usher type I syndrome) [44].…”
Section: Vestibular Functionmentioning
confidence: 99%